Developing a Life-Sized Version of Snakes and Ladders Game for Elementary School Students - Shafa Tara Kariyono (The Study Program of English Education of Palangka Raya University, 2026)
This study aimed to develop a life-sized Snakes and Ladders game as a learning medium for teaching English vocabulary and basic grammar (simple past and simple future tenses) to sixth-grade students at SDN Tulusrejo 04 Malang. The novelty of this study lies in the development of a life-sized, non-digital Snakes and Ladders game that integrates vocabulary and grammar learning through flexible card-based tasks, allowing students to participate as game pieces while actively engaging in language practice. The research followed the ADDIE model. The final product consisted of a 2.1m x 2.1m vinyl banner with 49 squares arranged in a 7x7 zig-zag pattern, a cardboard dice, and four sets of question cards: Past (20 cards), Future (20 cards), Job (20 cards), and Bonus (10 cards). The game was implemented with 15 sixth-grade students. Data were collected through expert validation sheets and a student questionnaire. The media and material experts gave scores of 86.15% and 80%, respectively, both categorized as Excellent. All students reported positive responses toward the game. The findings indicate that the game is a valid, practical, and engaging medium for teaching vocabulary and grammar in a low-resource elementary school setting.